2019
DOI: 10.1016/j.cell.2018.12.018
|View full text |Cite|
|
Sign up to set email alerts
|

Structural Basis of Nav1.7 Inhibition by a Gating-Modifier Spider Toxin

Abstract: Highlights d Spider toxin ProTx2 engages the Nav1.7 channel through a membrane access pathway d The toxin uses an electrostatic mechanism to oppose voltage sensor domain II activation d The toxin complexes with activated and deactivated states of voltage sensor domain II d A basis for electromechanical coupling in voltage-gated ion channels is revealed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
301
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(325 citation statements)
references
References 68 publications
21
301
2
1
Order By: Relevance
“…Notably, the key Na V PaS contact residues are not conserved in human Na V channels, which explains why Dc1a is insect‐selective . CryoEM and X‐ray crystallography have also been used recently to solve the structure of the complex formed between protoxin‐II, a spider‐venom knottin, and a chimeric bacterial/human Na V channel . These Na V channel‐knottin structures not only provide detailed information about the molecular basis by which these spider toxins allosterically modulate Na V channel activity, but they provide an opportunity for structure‐based rational design of knottins that are not only insect‐selective, but which target pest insects without harming beneficial species.…”
Section: Spider Knottins Allosterically Modulate Ion Channel Functionmentioning
confidence: 99%
“…Notably, the key Na V PaS contact residues are not conserved in human Na V channels, which explains why Dc1a is insect‐selective . CryoEM and X‐ray crystallography have also been used recently to solve the structure of the complex formed between protoxin‐II, a spider‐venom knottin, and a chimeric bacterial/human Na V channel . These Na V channel‐knottin structures not only provide detailed information about the molecular basis by which these spider toxins allosterically modulate Na V channel activity, but they provide an opportunity for structure‐based rational design of knottins that are not only insect‐selective, but which target pest insects without harming beneficial species.…”
Section: Spider Knottins Allosterically Modulate Ion Channel Functionmentioning
confidence: 99%
“…For photocrosslinking experiments and to reduce the complexity of working with full-length Nav1.7, we employed a chimera strategy in which hNav1.7 VSD2 sequences were fused to a NavAb scaffold to permit high-level expression and production of stable, purified protein (Ahuja et al, 2015;Xu et al, 2019). This chimeric channel is referred to as VSD2-NavAb and it was used in structural studies of Protoxin-II inhibition (Xu et al, 2019). A similar chimeric channel based on VSD2 and NavAb has exhibited binding to HwTx-IV in surface plasmon resonance assays (Rajamani et al, 2017).…”
Section: Design and Purification Of A Chimeric Vsd2-navabmentioning
confidence: 99%
“…Residue 27 potentially interacts with S3. The VSD2-NavAb structure originates from the cryo-EM studies of VSD2-NavAb in complex with ICK peptide Protoxin-II (Xu et al, 2019). mutagenesis studies probing the HwTx-IV binding site on Nav1.7, which showed that E753 in the VSD2 S1-S2 loop and E811 in VSD2 S3 were determined to be important residues (Xiao et al, 2011).…”
Section: Design and Purification Of A Chimeric Vsd2-navabmentioning
confidence: 99%
See 1 more Smart Citation
“…All α subunits share high sequence conservation and nearly identical structure topology. Thus, the design of isoform-selective Nav modulators is challenging [65]. Two centipede peptides, µ-SLPTX 3 -Ssm2a and µ-SLPTX 3 -Ssm3a, were identified as specific Nav blockers [42,66].…”
Section: Voltage-gated Sodium Channel (Nav) Blockermentioning
confidence: 99%